Cardiac Resynchronization Therapy in the Cardiorenal Syndrome - Margot K. Davis; Sean A. Virani (International Journal of Nephrology)
The cardiorenal syndrome (CRS) is a complex clinical syndrome in which dysfunction of either the heart or the kidneys affects the functioning of the other organ system. Many therapies used in heart failure have further detrimental effects on renal function. Cardiac resynchronization therapy (CRT) is a relatively new form of device therapy that reduces morbidity and mortality in patients with heart failure. This review will discuss the effects of CRT on renal function in patients with CRS, the impact of baseline renal function on response to CRT, and potential risks associated with CRT in this unique population.